Shalat sebagai Pilar Falsafah Islam : Pemahaman dan Praktik - Fiantika Armanda; Halisatul Muslimah; Dian Amelia Sari; Kurniati Kurniati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Prayer is a ritual of worship that has the most legal basis in the Qur'an that prayer is an obligation for every Muslim as a form of submission and obedience to Allah SWT. Prayer is a pillar of religion in Islam, prayer also has a certain time in carrying it out. Prayer is considered as a form that humans must surrender themselves completely to ask for guidance and help from Allah SWT. This article aims to explore the role of prayer as the main pillar and the practice of prayer in influencing the moral and ethical integrity of a Muslim in Islamic philosophy. This research uses library research methods to analyze the philosophy of prayer from the perspective of Islamic law. The research results show that there are still many individuals and groups who perform prayers only as an obligation or habit, without understanding the deeper meaning of this worship. This phenomenon shows negligence in the implementation of prayer, even though this worship should have a deep spiritual dimension. Prayer, as a means of direct connection with Allah SWT, should be the right time for a Muslim to complain, ask for forgiveness, and reflect. Apart from that, prayer also functions as a cleanser for the soul, preventing bad deeds, and bringing peace to a Muslim's heart. Therefore, it is important for Muslims to dig deeper into the meaning of prayer so that they can carry it out with full awareness and devotion.